(4/3 + x) × 7/4 = 5 - 7/6
\(\left(\frac{4}{3}+x\right).\frac{7}{4}=\frac{23}{6}\)
\(\frac{4}{3}+x=\frac{23}{6}:\frac{7}{4}\)
\(\frac{4}{3}+x=\frac{46}{21}\)
\(x=\frac{46}{21}:\frac{4}{3}\)
\(x=\frac{23}{14}\)
(4/3+x)x 7/4=23/6
(4/3+x=23/6:7/4
(4/3+x)=46/21
x=46/21- 4/3
x=6/7
(4/3+x)x7/4=23/6
4/3+x=23/6:7/4
4/3+x=46/21
x=46/21-4/3=6/7
( 4/3 + x) x 7/4= 23/6
(4/3+ x) = 23/6 :7/4
(4/3 +x ) = 46/21
x = 46/21- 4/3
x = 6/7
\(\left(\frac{4}{3}+x\right)\times\frac{7}{4}=5-\frac{7}{6}\)
\(\left(\frac{4}{3}+x\right)\times\frac{7}{4}=\frac{23}{6}\)
\(\frac{4}{3}+x=\frac{23}{6}:\frac{7}{4}\)
\(\frac{4}{3}+x=\frac{46}{21}\)
\(x=\frac{46}{21}-\frac{4}{3}\)
\(x=\frac{6}{7}\)
CHÚC BN HOK TỐT!